PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN DI PT. BANK MALUKU MALUKU UTARA CABANG TERNATE - Farnida Esa; Marwan Marwan; Nurlaila Nurlaila (Jurnal Manajemen Sinergi, 2020)
Objective: The purpose of this study are: (1) To determine andanalyze the effect of workload on employee performance at PT.Bank Maluku North Maluku Ternate Branch; (2) To find out andanalyze the effect of work stress on the performance ofemployees of PT. Bank Maluku North Maluku Ternate Branch;and (3) To find out and analyze the effect of workload and workstress on employee performance at PT. Bank Maluku NorthMaluku Ternate Branch. The number of research samples was43 employees. Bank Maluku North Maluku Ternate Branch.Methodology: The test equipment used is multiple linearregression analysis (multiple regression) using statisticalpackage for social scientists (SPSS) as a statistical test tool.Finding: H1 H2, and H3 are accepted at the 5% confidence levelConclusion: The results of the study show that: (1) workload hasa positive and significant effect partially on employeeperformance at PT. Bank Maluku North Maluku Ternate Branch.The results of this study mean that, employee workload is ableto improve employee performance; (2) Job stress has a positiveand significant effect partially on employee performance at PT.Bank Maluku North Maluku Ternate Branch. The results of thisstudy mean that, the work stress experienced by employees isable to improve employee performance; and (3) Workload andwork stress simultaneously have a positive and significant effecton PT. Bank Maluku North Maluku Ternate Branch.